Population mobility and urban wastewater dynamics - ATINKPAHOUN, N.H. Chrystelle; SOCLO, H. Henri (My University, 2018)
ABSTRACT Dynamic influent models, which have been proposed to test control strategies using virtual wastewater treatment plants, should be as realistic as possible. The number of inhabitants in the catchment at any given time and their ways of life are among the parameters affecting the quality of these models. Census data related to work and school commutes were used to evaluate the number of people present in a given urban area. Based on the example of a large urban catchment (Grand Nancy, France), the results show that a population increase of 30% could occur during working hours resulting from the imbalance between workers leaving and coming into the catchment. Combined with information related to the local way of life, variation in the population helps to explain changes inwastewater flowrate and pollution (carbon, nitrogen, phosphorus and heavymetals), which present several maxima reflecting daily activities, such as bladder voiding, meals, the use of washrooms, etc. However, no well-defined variation patterns for pH and conductivity,which are linked to the concentrations of anions and cations in thewastewater,were observed. Slight reductions (up to 10% on Sundays) in the flow and pollution loadwere observed onweekends as the commuter flowdecreased. Census data proved to be efficient in helping to understand the daily pattern of urban wastewater characteristics.
Keywords: Census; Commuter; Dynamics; pH; Wastewater